2020
DOI: 10.3390/molecules25204625
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical Method Using Ultra-High-Performance Liquid Chromatography Coupled with High-Resolution Mass Spectrometry (UHPL-CHRMS) for the Detection of Metformin in Human Plasma

Abstract: Metformin is the first-line medicine for the treatment of type 2 diabetes. Drug interactions between metformin and other drugs, food, or beverages cannot only cause changes in the pharmacokinetic profiles but also affect the efficacy of metformin. The purpose of this study was to develop a rapid and reliable bioanalytical method for the detection of plasma metformin concentration in humans. To remove interfering substances in plasma, acidified acetonitrile (acetonitrile containing 0.1% formic acid) was added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Metformin affects a host of cellular and physiological mechanisms, including glucose utilization, intracellular AMPK signaling, epithelial-mesenchymal (EMT) signaling, oxidative stress and inflammatory signaling, as well as other pathways [ 16 ]. The therapeutic oral dosage of metformin ranges from 500 up to 3000 mg/day depending on the specific disease and maximal metformin levels in human plasma do not exceed 39–50 µM [ 17 , 18 ]. There are a host of reports describing anticancer effects of metformin but in many cases concentrations of the drug were used that have no clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin affects a host of cellular and physiological mechanisms, including glucose utilization, intracellular AMPK signaling, epithelial-mesenchymal (EMT) signaling, oxidative stress and inflammatory signaling, as well as other pathways [ 16 ]. The therapeutic oral dosage of metformin ranges from 500 up to 3000 mg/day depending on the specific disease and maximal metformin levels in human plasma do not exceed 39–50 µM [ 17 , 18 ]. There are a host of reports describing anticancer effects of metformin but in many cases concentrations of the drug were used that have no clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin affects a host of cellular and physiological mechanisms, including glucose utilization, intracellular AMPK signaling, epithelialmesenchymal (EMT) signaling, oxidative stress and in ammatory signaling, as well as other pathways [16]. The therapeutic oral dosage of metformin ranges from 500 up to 3000 mg/day depending on the speci c disease and maximal metformin levels in human plasma do not exceed 39 -50 µM) [17,18]. There are a host of reports describing anticancer effects of metformin but in many cases concentrations of the drug were used that have no clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous search suggested that the studies used internal standard which is suitable for their studies [14]. Guaiphenesin is used as the internal standard for analyzing anti-diabetic drug in rat plasma [15], while others showing use of deuterated internal standards. Hence, internal standard should be chosen very carefully [16].…”
Section: Internal Standardmentioning
confidence: 99%